(untitled) (Boca Raton, 2014)
Aimed at producing and improving food ingredients, developments in food biotechnology have focused on the fields of genetics and in enzyme- and cell-based biological processes. While the underlying science of these developments and applications has traditionally been well reported, there is a clear lack of information on the engineering aspects of such biotechnology-based food processes. This book provides a comprehensive review of these aspects, from the development of food processes and products to the most important unit operations.
Keywords: Food,Thực phẩm; Biotechnology,Công nghệ sinh học